(untitled) (Culturas Científicas, 2022)
In recent years, some authors have argued that the validity of the arborescent representation of the phyletic pattern generated by evolution is being undermined by the recognition of the evolutionary impact of horizontal gene transfer (HGT), symbiogenesis, speciation by hybridization and introgression. This cladogenetic conception, or representation, of evolution would allow us to see only a partial aspect of the genealogical relationships that connect the different lineages of living beings; hiding another aspect whose more adequate representation would be a reticulation of relationships between taxa. However, even without questioning the frequency and explanatory relevance of such phenomena, this paper will try to show that their admission and recognition do not need to be detrimental for the cladogenetic conception of evolution whose relativization is being proclaimed. On the contrary, the understanding and representation of those phenomena presupposes that conception.